An Accounting Primer Circa 1831. - Jennings, Robert M.; Kistler, Linda H.; Mead, George C. (The Accounting Review, 1969)
The article discusses the investigation of accounting records. During an investigation of business records preserved in the manuscript section of the Baker Library at Harvard University Graduate School of Business, an early 19th century accounting primer was discovered. Various bookkeeping records and accounting procedures of mercantile companies operating during that period are outlined in the text. The book proved intrinsically interesting and also afforded the writer a useful guide to record keeping methods of early merchants. The purposes of this article are to describe the contents of the primer, to comment upon certain recording procedures of the early 1800's and to gain some insight into accounting methodology in the United States during this period. The value of the primer described in this paper is two-fold. First, the book is a valuable example of accounting instruction in the United States during the early 1800's. As such, it deserves recognition and preservation as an example of the evolution of accounting education and practice in the U.S. Second; students of business history would find the primer a useful preliminary study prior to examination of records of 19th century American businesses.